Analisis Kualitatif terhadap Motivasi Belajar Bahasa Inggris Siswa di Alue Pineung Timue Kota Langsa - Dede Gustian (Penerbit Goodwood, 2024)
Purpose: This study aims to analyze the factors that influence English learning motivation among students in rural areas using a qualitative approach. Research methodology: Data were collected through in-depth interviews, observations, and document analysis in several junior high schools in Alue Pineung Timue, Langsa City. Results: The results of the study indicate that students' learning motivation is influenced by various social, economic, and cultural factors. Family environment, school support, economic conditions, and students' perceptions of the relevance and difficulty of English are the main determinants of their motivation levels. Less positive learning experiences and negative perceptions of English as a difficult subject that is not relevant to everyday life hinder students' motivation.